Integrative Medicine for Gastrointestinal Disease - Dossett, Michelle L. (Prim Care, 2017)
Gastrointestinal conditions are prevalent in the population and account for significant morbidity and healthcare costs. Patients with gastrointestinal conditions frequently use integrative medicine. There is growing evidence that integrative medicine approaches can improve symptoms and, in some cases, directly affect physiology and disease course. In this article we review the data on some of the most common and well-studied approaches including mind-body therapies, acupuncture, diet, probiotics, and other dietary supplements and herbs in gastroesophageal reflux disease, inflammatory bowel disease, irritable bowel syndrome, non-alcoholic fatty liver disease, and nausea and vomiting. While clear recommendations can be made for some conditions, in others there are challenges in translating these findings due to small study size, lack of standardization, and trial heterogeneity.